DESAIN SISTEM INFORMASI RANTAI PASOK TERINTEGRASI BERBASIS ENTERPRISE RESOURCE PLANNING ODOO PENJUALAN - Velica Yoyellia; Deasy Kartika Rahayu Kuncoro; Yandra Arkeman (Industry Xplore, 2024)
ERP systems have become a part of companies, so all the processes of business activities within the company are integrated with each other. Currently, many vendors offer ERP systems that are inexpensive and easy to implement, such as OpenERP or Odoo, which are open-source ERP systems. This study aims to identify the need for a sales information system that can solve problems at the company, design a sales information system that fits the needs of users based on ERP, and know the effectiveness of using the Odoo Sales Module application in the system. The method used is descriptive quantitative, namely by filling out a questionnaire for the sales staff to test the application using the User Acceptance Test (UAT). The results showed that the average UAT score was 90%. This value indicates that the respondents strongly agree that the Odoo Sales Module application is very useful and easy to use.